Comprehension of Emblems of Medicine among Medical Students of Rawalpindi - Rija Kunwar, Rija Kunwar; Rumaisa Maryam, Rumaisa Maryam; Nadia Khalid, Nadia Khalid; Tehzeeb ul Hassan, Tehzeeb ul Hassan (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: The Caduceus is the popular representation of medicine. However, major health organizations and regulatory bodies such as the WHO use a different symbol- the Rod of Asclepius in their logo. Materials and Methods: This cross-sectional study was undertaken in Rawalpindi Medical College after approval from Institutional Review Forum. The study population consisted of equal percentage of medical students from all the academic years of Rawalpindi Medical College. The data was collected using the technique of stratified random sampling. Stratification was done based on both gender and academic years of the study. A pre-tested semi-structured questionnaire was administered to them. The data was analysed using SPSS version 23. Information regarding the symbols was assessed. For all categorical variables like gender, academic year, representation etc. frequencies along with percentages were calculated. Results: Only 19.3% of students knew that Rod of Asclepius was the true symbol of medicine. Most of the students (52%) thought that the Caduceus was the true symbol of medicine. 23.3% responded by stating that both were the emblems of medicine while some (5.5%) students responded that none of them represented medicine. Regarding Rod of Asclepius, only 38.39% of the students stated correctly that it represented medicine and healing, while majority of students (50.89%) stated that it represented danger and death followed by hospitals (6.25%) and commerce (4.46%). For the Caduceus, only (9.82%) knew that it represented commerce while the majority of students (61.6%) stated that it represented medicine and healing followed by danger and death (17.0%) and hospitals (11.6%). Conclusions: There is very little awareness about the rod of Asclepius and most institutions have adopted a logo based on the Caduceus. Awareness of the true origins and the symbolism of the emblems is lacking in the medical fraternity. Keywords: Rod of Asclepius, Caduceus